1998
DOI: 10.1021/bi972548x
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Function Studies of Ligand-Induced Epidermal Growth Factor Receptor Dimerization

Abstract: We present a novel 96-well assay which we have applied to a structure-function study of epidermal growth factor receptor dimerization. The basis of the assay lies in the increased probability of EGFRs being captured as dimers by a bivalent antibody when they are immobilized in the presence of a cognate ligand. Once immobilized, the antibody acts as a tether, retaining the receptor in its dimeric state with a resultant 5-7-fold increase in binding of a radiolabeled ligand probe. When the assay was applied to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…1D) for the EGFR-FLuc reporter degradation. This compared favorably to the known EC 50 of 16 ng/mL for EGF-induced EGFR dimerization documented in the literature (26). Consequently, a saturating concentration of EGF (100 ng/mL) was used in all subsequent experiments.…”
Section: Resultsmentioning
confidence: 66%
“…1D) for the EGFR-FLuc reporter degradation. This compared favorably to the known EC 50 of 16 ng/mL for EGF-induced EGFR dimerization documented in the literature (26). Consequently, a saturating concentration of EGF (100 ng/mL) was used in all subsequent experiments.…”
Section: Resultsmentioning
confidence: 66%
“…In the present study, EGF and betacellulin worked well at 10 ng/ml, whereas amphiregulin was not effective at 10 ng/ml, but was effective at 1000 ng/ml. This difference in the effective concentration may be due to the difference in binding affinity, since the affinity of amphiregulin is several orders of magnitude less than that of EGF [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, EGF and betacellulin worked well at 10 ng/ml, whereas amphiregulin was not effective at 10 ng/ml, but was effective at 1000 ng/ml. This difference in the effective concentration may be due to the difference in binding affinity, since the affinity of amphiregulin is several orders of magnitude less than that of EGF [26,27].Furthermore, it is very interesting that a combination of EGF with another EGF-family member (amphiregulin or betacellulin), as compared with EGF alone, improved the percentage of oocytes developing to the metaphase-II stage. A similar synergistic effect on oocyte maturation has been observed in buffalo COCs exposed to EGF plus IGF-I [28].…”
mentioning
confidence: 99%
“…Soluble AREG directly binds to EGFR as a ligand to transmit growth signal (3). However, AREG is not able to activate EGFR signaling effectively compared with other EGFR ligands (4). It is well established that AREG translocates to the plasma membrane; however, few reports showed that AREG localizes in the nucleus (5,6).…”
mentioning
confidence: 99%